Health Information Counselors: A New Profession for the Age of Big Data. (January 2019) - Fiske, Amelia; Buyx, Alena; Prainsack, Barbara
Abstract : Health care is increasingly data driven. Concurrently, there are concerns that health professionals lack the time and training to guide patients through the growing medical "data jungle." In the age of big data, ever wider domains of people's lives are "datafied, " which renders ever more information—at least in principle—usable for health care purposes. Turning data into meaningful information for clinical practice—and deciding what data or information should not be used for this purpose—requires a significant amount of time, resources, and skill. The authors argue that academic medicine should lead the way in navigating the use of complex, highly personal data in clinical practice. To make data actionable for both clinicians and patients, the authors propose that the best way to navigate the interface between patients and providers in the era of data-rich medicine would be the creation of a new profession entirely: health information counselors (HICs). HICs would have broad knowledge of various kinds of health data and data quality evaluation techniques, as well as analytic skills in statistics and data interpretation. Trained also in interpersonal communication, health management, insurance systems, and medico-legal aspects of data privacy, HICs would know enough about clinical medicine to advise on the relevance of any kind of data for prevention, diagnosis, and treatment. The creation of this new specialty would help patients and health care professionals to make more informed choices about how increasing amounts of health data and information can or should inform health care.